2016
DOI: 10.3389/fpsyg.2016.00473
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Dynamic Attunement of Speech and Gestures in the Construction of Children’s Understanding

Abstract: As children learn they use their speech to express words and their hands to gesture. This study investigates the interplay between real-time gestures and speech as children construct cognitive understanding during a hands-on science task. 12 children (M = 6, F = 6) from Kindergarten (n = 5) and first grade (n = 7) participated in this study. Each verbal utterance and gesture during the task were coded, on a complexity scale derived from dynamic skill theory. To explore the interplay between speech and gestures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 98 publications
1
19
0
Order By: Relevance
“…Such spectral decomposition approaches help quantify and correlate gesture and speech activity that happens on the syllable, clause, and sentence time scales. Others have used approaches in dynamical systems research, whereby changes in temporal structures of categorical events or continuous time series (recurrence quantification analysis, or RQA; Wallot, 2017;Webber & Marwan, 2015) are the object of study as opposed to averaged metrics of speech or gesture activity (De Jonge-Hoekstra, Van der Steen, Van Geert, & Cox, 2016;Fusaroli & Tylén, 2016;Pouw, De Jonge-Hoekstra, & Dixon, 2018). These RQA approaches are especially potent for understanding global gesture patterns that reflect stability of recurrent behavior through a time-dependent analysis of local fluctuations in gesture activity.…”
Section: The Study Of Gesture As a Multi-scale Phenomenonmentioning
confidence: 99%
See 1 more Smart Citation
“…Such spectral decomposition approaches help quantify and correlate gesture and speech activity that happens on the syllable, clause, and sentence time scales. Others have used approaches in dynamical systems research, whereby changes in temporal structures of categorical events or continuous time series (recurrence quantification analysis, or RQA; Wallot, 2017;Webber & Marwan, 2015) are the object of study as opposed to averaged metrics of speech or gesture activity (De Jonge-Hoekstra, Van der Steen, Van Geert, & Cox, 2016;Fusaroli & Tylén, 2016;Pouw, De Jonge-Hoekstra, & Dixon, 2018). These RQA approaches are especially potent for understanding global gesture patterns that reflect stability of recurrent behavior through a time-dependent analysis of local fluctuations in gesture activity.…”
Section: The Study Of Gesture As a Multi-scale Phenomenonmentioning
confidence: 99%
“…This question can now be addressed quantitatively via gesture network analysis. Given that we have two datasets where participants spoke a different language, namely the American-English DAF dataset (Pouw & Dixon, 2018) and the German SAGA dataset (De Jonge-Hoekstra et al, 2016;Lücking et al, 2010), we could approach this question via network analyses, and specifically we might want to use dichotomized adjacency networks for this. Before we proceed, it is however important to note that these results are not conclusive in any way as the current datasets are different in a number of ways next to the difference in spoken language.…”
Section: Groups Of Speakersmentioning
confidence: 99%
“…It has been recently proposed that the directionality of the asymmetry between vertical and horizontal lines in a recurrence plot can provide complementary information about the coupling of two subsystems (Cox et al, 2016 ). De Jonge-Hoekstra et al ( 2016 ) applied cross-recurrence to analyse gestures and speech data streams recorded in children during a hands-on science task and found that in 5-year-old children such asymmetry in the resulting recurrence plots suggests that speech categories attract gesture categories at the same level of abstraction in a more dynamically stable fashion than vice versa . They also showed that gestures and speech are more synchronized when children grow older.…”
Section: Methodsmentioning
confidence: 99%
“…Cross-Recurrence Quantification Analysis (C-RQA) is used with signals coming from two interacting systems [44][45][46][47][48][49][50]. C-RQA, like RQA, quantifies coordinative patterns based on an analysis of the sequence of behaviours performed in real time [40,41].…”
Section: Complexitymentioning
confidence: 99%
“…In psychology, such signals can be fluctuations in gait, postural changes, eye movements, or informational patterns, such as syntactic structures or words exchanged by two persons during a communicative interaction. In fact, there is a large corpus of evidence in which these nonlinear techniques have been used to analyse postural fluctuations [42], conversational interaction between caregiver and child [34,51,52], coupling of time series of verbalizations and gestures [50], and reading comprehension [53]. Additionally, Complexity 5 through these analyses, interpersonal coordination has been characterized in terms of coupling of eye movements [42], body movements [41,54], child behaviour and sleep [55], patterns of aggression [29], minimal and effective forms of coordination during the dialogue [4], and early language development [46,47].…”
Section: Complexitymentioning
confidence: 99%